Pedagogical Support for the Educational Technology Learning Program [Protea]1: A Constructivist Experience Using Makey Makey and Scratch for Enrichment Purposes in a Musical Expression Course - Castro Araya, Hazel (2020)
This article depicts teacher experience within the framework of the Educational Technology Learning Program [Protea] at the University of Costa Rica Department of Education as part of the program: Innovative Teaching: Leveraging on ICTs for Education which was the result of a collaborative effort during the 1st semester of 2017. The program is aimed at developing pedagogical experiences that leverage on digital technology for purposes of music education, specifically in a course on Musical Expression for Beginning Education Level II for Preschool Education majors. The objective of this article is to analyze teacher experience consisting of the design and development of an educational project that uses Maky Makey and Scratch. The project looks at how technology can impact how Music Education is taught and is, specifically directed at University of Costa Rica Preschool Education majors.  The workshop consisted of 30 students enrolled in the course, Musical Expression FD-0173 for Preschoolers. A Project-Based Learning [PBL] methodology was used with a constructivist focus. Research consisted of reflections from the Protea staff regarding  the contributions made by learning technology as well as the course instructor with regards to disciplinary expertise. Results focus on promotion of logical-mathematical thought, teamwork, problem-solving and linkages between technology and Music Education. For this purpose, students worked on a large array of proposals using educational material with different complexity levels for Preschoolers in order to facilitate assessment of possibilities and innovations both in Education and Technology.